Modeli književnega pouka v slovenskem šolskem sistemu - Krakar-Vogel, Boža (Jezik in slovstvo, 2019)
The article presents various views on literature teaching in Slovenian grammar schools (gimnazija) as they have developed from the second half of the 1970s until today. It presents some of the models that have been created and shows how they have been integrated into teaching practice during school reforms. On the basis of existing research, a summary is given of the current situation with regard to literature teaching in grammar schools and some guidelines are offered for the future.
Keywords: diferenciacija; eksterna matura; gimnazije; književnost; komunikacijski pouk; pouk književnosti; recepcijska didaktika književnosti; sistemska didaktika knjževnosti